Os efeitos de um ato de concentração, a interação estratégica entre firmas e a política antitruste: simulações, evidências, análises e críticas - Marina Moreira da Gama (2010)
This thesis addressed two issues, the mergers effects and the strategic interaction among firms, in order to, firstly, study the causes and consequences of these effects and suggest methods to measure them, and secondly, make a contribution on how strategic interaction is treated in Industrial Organization. In the opening chapters was possible to present the method that measures the unilateral effects, the merger simulation, and show that, besides its quantitative results that facilitate the antitrust trial, it is open to criticism: the results sensitivity to the demand system and oligopoly model chosen and the ignorance of the possibility of collusive behavior. Because of that, on the forth chapter, we made an attempt to deepen the cooperations study using a genetic algorithm to simulate the Iterative Prisoner's Dilemma, which results in terms of the emergence of cooperation due to a mutual confidence gain between players after numerous and repeated interactions. Then, in the fifth chapter, a basic evolutionary model of strategic interaction among firms and a computer simulation based on agents built bottom-up show how important are structural and conduct variables to analyze the emergence and evolution of cooperation. Then, given the unilateral and coordinated effects similar findings in terms of price and profitability increases, a closer examination of the strategic interaction among firms in a market should be held to highlight the collusion possibility. Key-Words: merger effects; strategic interaction; computer simulation